Squaring the circle in Euroland? Some remarks on the Stability and Convergence Programmes 2010-2013 - Till van Treeck; Silke Tober; Achim Truger; Michael Brecht (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2010)
It is generally held, from both a global and a European perspective, that the three most impor-tant objectives for the years to come are 1) the reduction of current account imbalances, 2) the reduction of public deficits, and 3) the reduction of unemployment. This paper argues that the Stability and Convergence Programmes (SCPs) for the period 2010-2013, submitted by the euro area member states to the European Commission in January/February 2010, will not achieve all three objectives. Indeed, under current circumstances, the simultaneous realisation of these objectives would be like "squaring a circle". We show that the SCPs rely on rather optimistic assumptions about private sector demand and GDP growth, given the degree of fiscal consolidation. At the same time, they imply that current account imbalances in EMU would remain quite significant until 2013. Our analysis is mainly based on a few simple accounting identities and places special emphasis on Germany. It leads us to conclude that, in the absence of a drastic deterioration of private financial balances, the only way to achieve the GDP growth rates projected in the SCPs (and, ideally, current account rebalancing) would be for the governments of surplus countries to be prepared to run higher deficits over the next few years. This would be more "fiscally responsible" than the current focus on deficit reduc-tion. Failure to do so may result in persistently high unemployment in the years to come and may threaten the European Monetary Union.
urn:nbn:de:101:1-201101312819
Keywords: 330; Europäischer Stabilitätsmechanismus; Entwicklungskonvergenz; Wirtschaftspolitisches Ziel; Leistungsbilanz; Außenwirtschaftliches Gleichgewicht; Haushaltskonsolidierung; Arbeitsmarktpolitik; EU-Staaten; Deutschland